Breast-specific gamma imaging with Tc-99m-sestamibi in the diagnosis of breast cancer and its semiquantitative index correlation with tumor biologic markers, subtypes, and clinicopathologic characteristics. Issue 8 (August 2016) - Tan, Hui; Zhang, Hongwei; Yang, Weige; Fu, Yipeng; Gu, Yusen; Du, Min; Cheng, Dengfeng; Shi, Hongcheng
Abstract : Objectives: To determine the sensitivity of breast-specific gamma imaging (BSGI) in diagnosing breast cancer and assess the potential correlation between the semiquantitative index of BSGI and biologic markers, molecular subtypes, and clinicopathologic characteristics of breast cancer. Materials and methods: The sensitivity of BSGI for breast cancer was retrospectively assessed in 102 female breast cancer patients who underwent BSGI before surgery and was compared with that of ultrasonography and mammography. BSGI was visually graded on the basis of the Society of Nuclear Medicine and Molecular Imaging guideline. Tracer uptake in the cancer as the lesion to nonlesion ratio (L/N) was calculated semiquantitatively and was subsequently correlated to tumor biologic markers, molecular subtypes, and clinicopathologic characteristics. Results: The sensitivity of BSGI for breast cancer by visual analysis was 94.1% (96/102) in our cohort, which was 100% (47/47) in the subgroup of patients with a tumor size more than 2.0 cm and 89.1% (49/55) in the subgroup of patients with a size less than or equal to 2.0 cm. The sensitivity of BSGI was significantly higher than that of ultrasonography of 84.2% (85/101) ( P =0.022) and mammography of 84.5% (60/71) ( P =0.037). There was no significant correlation between the L/N and expressions of estrogen receptor, progesterone receptor, human epidermal growth factor receptor 2, and antigen Ki-67, and the subtypes or histologic grade of the cancer ( P >0.05). However, the value of L/N was associated with infiltration degree ( P =0.005), axillary lymph node status ( P =0.029), and tumor size ( P =0.002). Multivariate analysis further indicated that the value of L/N was correlated with infiltration degree ( P =0.016) and tumor size ( P =0.002). Conclusion: BSGI has a high sensitivity for detecting primary breast cancer. The value of L/N on BSGI was independently related to infiltration degree and tumor size of breast cancer, but not to expression of tumor receptor markers and histologic grade.